KINERJA MESIN AIR-WATER HARVESTER DENGAN SUSUNAN EVAPORATOR PARALEL PASA BERBAGAI KECEPATAN UDARA MASUK - Mirmanto; Nurchayati; Nurpatria; Ahmad Sofa Amrillah (Energy, Materials and Product Design, 2026)
During the dry season, several regions in Indonesia experience drought conditions and limited access to clean water. An air-water harvester system offers a potential solution, as it utilizes flexible air conditioning (AC) components and can be implemented in various locations provided that an adequate power supply is available. This study aims to investigate the effect of inlet air velocity on water production and heat transfer rate in an air-water harvester system. An experimental approach was employed with inlet air velocity variations of 0 m/s, 1.5 m/s, and 3 m/s. The system utilized three evaporators constructed from 12U refrigerator condensers, a 1 PK compressor, and R-134a refrigerant. Experiments were conducted over a period of nine days, from 09:00 to 16:00 each day. The results indicate that increasing inlet air velocity enhances both water production and heat transfer rate. The highest average water yield was 1.676 kg over a 7-hour period at an air velocity of 3 m/s. In addition, the maximum average total heat transfer rate absorbed by the evaporator reached 295.98 W under the same air velocity condition.